Protection against neurotoxicity by an autophagic mechanism - Liu,Kangyong (2012)
The objective of the present study was to investigate the effects of 3-n-butylphthalide (NBP) on a 1-methyl-4-phenylpyridinium (MPP+)-induced cellular model of Parkinson’s disease (PD) and to illustrate the potential mechanism of autophagy in this process. For this purpose, rat PC12 pheochromocytoma cells were treated with MPP+ (1 mM) for 24 h following pretreatment with NBP (0.1 mM). Cell metabolic viability was determined by the MTT assay and cell ultrastructure was examined by transmission electron microscopy. The intracellular distribution and expression of α-synuclein and microtubule-associated protein light chain 3 (LC3) were detected by immunocytochemistry and Western blotting. Our results demonstrated that: 1) NBP prevented MPP+-induced cytotoxicity in PC12 cells by promoting metabolic viability. 2) NBP induced the accumulation of autophagosomes in MPP+-treated PC12 cells. 3) Further study of the molecular mechanism demonstrated that NBP enhanced the colocalization of α-synuclein and LC3 and up-regulated the protein level of LC3-II. These results demonstrate that NBP protects PC12 cells against MPP+-induced neurotoxicity by activating autophagy-mediated α-synuclein degradation, implying that it may be a potential effective therapeutic agent for the treatment of PD.